Personal Strengths of Russian Teachers in VIA Model: Approbation of the Russian-Language Version of the Questionnaire "Values in Action Inventory of Strengths" (VIA - IS120) - Alexey A. Stavtsev; Arthur A. Rean; Roman G. Kuzmin (National Research Mordova State University, 2021)
Introduction. Positive psychology is one of the most rapidly developing directions of psychological science in the world. Over the past two decades, a large number of empirical researches confirm effectiveness and validity of theoretical studies and practical methods used in the framework of positive psychology. Unfortunately, there is a lack of research in this area in the Russian-speaking scientific community, despite of the presence of high-level scientific teams and individual researchers working in the framework of positive psychology. Probably an important factor in the "low popularity" of positive psychology among Russian authors is the lack of large-scale studies on wide samples of Russian respondents. The purpose of this article is to empirically confirm, the legitimacy of the practical application of the "VIA" model. As well as perform approbation, validation and publication of the Russian-language version of the questionnaire by K. Peterson and M. Seligman "Values in Action Inventory of Strengths" in Russian we suggest more reflecting the essence of the questionnaire name - "24 strengths of the personality". Materials and Methods. The approbation was carried out on a wide sample of respondents from the professional sphere of education (N = 7 946), using statistical methods for checking the reliability of the questionnaire, including convergent validity and confirmatory factor analysis. Results. The reliability tests showed significant validity results, indicating the reliability of the psychometric tool. The scales of the Russian-language version of the VIA-IS questionnaire show more than sufficient internal consistency, The convergent validity test showed significant correlations with the following scales: Life Satisfaction Scale, Self-Esteem Scale, General Self-Efficiency Scale, and Professional Burnout (Maslach's). Confirmatory factor analysis confirmed the factorial structure of the questionnaire. We manage to meet the desirable "cut-off" model fit parameters of Confirmatory factor analysis. Discussion and Conclusion. Hopefully, publication of this Russian-language questionnaire will lead to an increase interest for research in the field of positive psychology in the Russian scientific community. The conclusions made by the authors contribute to the development of theoretical concepts of positive psychology, confirming the general structural integrity and practical validity of the model "VIA". Moreover, this article provides for open use in the Russian scientific psychological community a universal psychometric technique in form of questionnaire with empirically proven reliability on a wide sample of respondents.